LC‐MS/MS method for the determination of agomelatine in human plasma and its application to a pharmacokinetic study. (5th August 2013) - Wang, Xiaolin; Zhang, Dan; Liu, Man; Zhao, Hongna; Du, Aihua; Meng, Lingjie; Liu, Huichen
ABSTRACT: A sensitive and selective LC‐MS/MS method for the determination of agomelatine in human plasma was developed and validated. After simple liquid–liquid extraction, the analytes were separated on a Zorbax SB‐C18 column (150 × 2.1 mm i.d., 5 µm) with an isocratic mobile phase consisting of 5 mm ammonium acetate solution (containing 0.1% formic acid) and methanol (30:70, v/v) at a flow‐rate of 0.3 mL/min. The MS acquisition was performed in multiple reaction monitoring mode with a positive electrospray ionization source. The mass transitions monitored were m/z 244.1 → 185.3 and m/z 285.2 → 193.2 for agomelatine and internal standard, respectively. The methods were validated for selectivity, carry‐over, matrix effects, calibration curves, accuracy and precision, extraction recoveries, dilution integrity and stability. The validated method was successfully applied to a pharmacokinetic study of agomelatine in Chinese volunteers following a single oral dose of 25 mg agomelatine tablet. Copyright © 2013 John Wiley & Sons, Ltd.